2012
DOI: 10.1007/s00268-012-1576-2
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Comparison Study of Two Noncrosslinked Biologic Meshes Used in Complex Ventral Hernia Repairs

Abstract: These preliminary data demonstrate promising short-term outcomes for high-risk complex hernias repaired with biologic mesh, particularly SurgiMend, but the long-term durability of these biological materials is yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…[26][27][28] In a retrospective chart review of outcomes in 35 high-risk ventral herniorrhaphy patients, Janfaza et al found that rates of postoperative infection and hernia recurrence at 1 year were lower in patients who received a neonatal bovine mesh implant (SurgiMend, TEI Biosciences, Boston, Massachusetts) (17% and 5%, respectively) compared with patients who received a humanderived mesh (Flex HD, Ethicon Inc, Somerville, New Jersey) (50% and 33%, respectively). 26 In a large prospective chart analysis of .33,000 patients from the US National Surgical Quality Improvement Program (NSQIP) who underwent ventral hernia repair, Choi et al found that patients with some level of operative field contamination were three-to fivefold more likely to experience postoperative complications than those with clean surgical fields. 27 However, it is not possible to decipher whether the type of mesh applied (synthetic versus biologic) influenced such outcomes in Choi's analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In a retrospective chart review of outcomes in 35 high-risk ventral herniorrhaphy patients, Janfaza et al found that rates of postoperative infection and hernia recurrence at 1 year were lower in patients who received a neonatal bovine mesh implant (SurgiMend, TEI Biosciences, Boston, Massachusetts) (17% and 5%, respectively) compared with patients who received a humanderived mesh (Flex HD, Ethicon Inc, Somerville, New Jersey) (50% and 33%, respectively). 26 In a large prospective chart analysis of .33,000 patients from the US National Surgical Quality Improvement Program (NSQIP) who underwent ventral hernia repair, Choi et al found that patients with some level of operative field contamination were three-to fivefold more likely to experience postoperative complications than those with clean surgical fields. 27 However, it is not possible to decipher whether the type of mesh applied (synthetic versus biologic) influenced such outcomes in Choi's analysis.…”
Section: Discussionmentioning
confidence: 99%
“…SurgiMend (TEI Biosciences Inc, Boston, USA), a xenogenic acellular derma matrix derived from fetal bovine dermis tissue, was originally used for hernia repair [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Difficult cases involving radiated or contaminated wounds are facilitated by acellular dermal matrices (ADMs), boasting overall success rates greater than 90% 2. In the setting of infected surgical fields, these biological materials aid the healing process by promoting host collagen deposition and neovascularisation 3. While heterotopic ossification (HO) in abdominal incisions has been well documented, we report an interesting case of a hernia repair using fetal bovine ADM, which to our knowledge is the first case of heterotopic bone formation involving the whole of a biological mesh.…”
Section: Introductionmentioning
confidence: 99%